Longy : Booze, Brawls, Sex and Scandal - The Autobiography of the Wild Man of Rugby League - Long, Sean, 1976- and Appleyard, Nick (London John Blake, 2009)
Sean Long is Super League's No 1. bad boy, and when it comes to off-the-pitch madness, no one comes close. Here, the flamboyant St. Helens superstar tells his hilarious, shocking, and explosive life story--packed with amazing tales of booze, brawls, sex, and scandal. The only player to win the Lance Todd Trophy three times tells the inside story of that bet against his own team and exposes secrets that will shock the rugby league establishment to its core. In his own words, he describes with startling honesty the hellraising experiences of his rag-to-riches journey. But it isn't all about his w.
Include Color Illustration
Keywords: Rugby League football players -- Great Britain -- Rugby League football players -- Great Britain -- Biography